1993
DOI: 10.1021/ed070pa133
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide and its determination in the atmosphere: A simple method for surveying ambient pollution concentrations

Abstract: Expensive instruments are often required in order to pursue questions of student interest in determining pollution concentrations. The author provides inexpensive means for introducing students to air-pollution detection and measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…However, a further wind tunnel experiment with the TEAcoated meshes used in the first prototype showed that the NO 2 concentrations in the TEA reached equilibrium after being exposed for two days to a continuous air stream containing normal indoor concentrations of NO 2 at a wind velocity of 2.0 m s À1 . Considering that the chemical stoichiometry between TEA and NO 2 is 1 : 1, [12][13][14][15][16] the amount of TEA coated on the meshes (on average $6 mg, $4.2 Â 10 À5 mol) might not have been enough to sample the NO 2 contained in the air stream ($5.8 Â 10 À3 mol), even though the sampling efficiency was less than 1%. 11 Therefore, the mesh-based sampler appears to become effectively saturated in a short time period of a few days, which will make it unsuitable for longer-term (time-integrated) exposure studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a further wind tunnel experiment with the TEAcoated meshes used in the first prototype showed that the NO 2 concentrations in the TEA reached equilibrium after being exposed for two days to a continuous air stream containing normal indoor concentrations of NO 2 at a wind velocity of 2.0 m s À1 . Considering that the chemical stoichiometry between TEA and NO 2 is 1 : 1, [12][13][14][15][16] the amount of TEA coated on the meshes (on average $6 mg, $4.2 Â 10 À5 mol) might not have been enough to sample the NO 2 contained in the air stream ($5.8 Â 10 À3 mol), even though the sampling efficiency was less than 1%. 11 Therefore, the mesh-based sampler appears to become effectively saturated in a short time period of a few days, which will make it unsuitable for longer-term (time-integrated) exposure studies.…”
Section: Introductionmentioning
confidence: 99%
“…NO 2 À can then diazotise sulfanilamide and the resulting diazonium salt couples with N-(1-naphthyl)ethylenediamine dihydrochloride (NEDA) to form a purple azo dye which can be analysed colorimetrically. [12][13][14][15]…”
mentioning
confidence: 99%
“…The chemical analytical method was similar to that of other studies. 5,[10][11][12] 3.000 ml of 2% (w/v) solution of sulfanilamide (AnalaR, VWR International Ltd., England) in 5% (v/v) orthophosphoric acid (85.0%, BDH Laboratories, England) and 0.150 ml of 0.14% w/w solution of N-(1-naphthyl)ethylenediamine dihydrochloride (NEDA) (AnalaR, VWR International, Ltd.) were added into each amber vial containing the samples. The vials were then re-capped, shaken vigorously for half a minute, and left to stand for 5 min before the solution was analysed on a UV/vis-spectrophotometer (CE 1011, CECIL Instruments, UK) for light absorbance at a wavelength of 540 nm.…”
Section: Field Deployment Sampling and Analysismentioning
confidence: 99%
“…Nitrogen dioxide, NO 2 , produced as a byproduct of high temperature flames in internal combustion engines (2) can form acid rain and photochemical smog that pollute the environment. The second is a passive sampler that requires a relatively long sampling time (5,6). In general, two major types of sampling devices are available.…”
mentioning
confidence: 99%